Faktor Yang Berhubungan Dengan Pemberian Mp-Asi Pada Bayi 0-6 Bulan Di BPM Romauli Silalahi - Maulidanita, Riska (Window of Health : Jurnal Kesehatan, 2020)
Complementary feedings are foods or drinks that are given in diverse ways to infants other than breast milk. One of the factors that cause mothers to provide complementary feeding to infants aged 0-6 months is due to knowledge, attitude, work, and family support. This study aimed to determine the relationship of knowledge, attitudes, work, and family support with complementary feeding for infants 0-6 months at Bidan Praktek Mandiri Romauli Silalahi Clinic. Research used analytical survey with cross-sectional approach. The populations were all women who gave birth. The sampling using the total population as a sample as many as 34 people. Data retrieval used secondary data and tested by chi-square at a 95% confidence level. The research result that there was a relationship with complementary feeding of infants aged 0-6 months with knowledge of getting Ï-value = .033 <.05, attitudes obtained Ï-value = .002 <.05, family support obtained Ï-value = .011 (<.05) , and the work obtained Ï-value = .024 (<.05). Conclusion: Shows that there is a relationship of knowledge with complementary feeding for infants aged 0-6 months, there is a relationship between attitude to complementary feeding for infants aged 0-6 months, there is a relationship between family support and complementary feeding for infants 0-6 months, there is a working relationship with complementary feeding for infants 0-6 months.